Therapeutic Strategies for Mitigating Driving Risk in Patients with Narcolepsy - McCall CA; Watson NF (Dove Medical Press, 2020)
Catherine A McCall,1,2 Nathaniel F Watson3 1Department of Pulmonary, Critical Care, and Sleep Medicine, VA Puget Sound Health Care System, Seattle, WA, USA; 2Department of Psychiatry and Behavioral Sciences, University of Washington Sleep Medicine Center, Seattle, WA, USA; 3Department of Neurology, University of Washington Sleep Medicine Center, Seattle, WA, USACorrespondence: Catherine A McCallVA Puget Sound Health Care System, 1660 S. Columbian Way, Seattle, WA 98108, USAEmail cmccall1@uw.eduAbstract: Narcolepsy is a central nervous system hypersomnia disorder characterized by uncontrollable episodes of daytime sleep, sleep state instability, and cataplexy (sudden loss of muscle tone precipitated by emotion). Individuals with narcolepsy report more frequent sleep-related crashes, near crashes, and drowsy driving than drivers with other sleep disorders. As such, evaluating risk of sleep-related crashes is of great importance for this patient population. There are no established guidelines for ensuring driving safety in patients with narcolepsy; however, many providers currently use a combination of subjective report, report of prior crashes or near-misses, report of previously falling asleep while driving, sleepiness screening tools, and maintenance of wakefulness testing (MWT) to determine risk. Driving simulator tests, though often unavailable to the clinician, provide data to support the use of MWT for evaluation of alertness in drivers with narcolepsy. Treatments such as modafinil may improve driving performance; however, the impact of other treatments such as stimulants and sodium oxybate on driving has not been extensively studied. Behavioral and lifestyle modifications may also reduce risk, including scheduled naps, driving only short distances, and avoiding driving after meals, sedating medications, and alcohol intake. Even with effective treatment, alertness in patients with narcolepsy may never reach that of normal drivers; however, studies have suggested that narcolepsy patients may be able to drive safely with appropriate limitations.Keywords: narcolepsy, cataplexy, driving, safety